SMAC-FDI: A single model active fault detection and isolation system for unmanned aircraft - Ducard, Guillaume J.J. (Zielona Góra: Uniwersytet Zielonogórski)
This article presents a single model active fault detection and isolation system (SMAC-FDI) which is designed to efficiently detect and isolate a faulty actuator in a system, such as a small (unmanned) aircraft. This FDI system is based on a single and simple aerodynamic model of an aircraft in order to generate some residuals, as soon as an actuator fault occurs.
Keywords: fault detection and isolation; unmanned aerial vehicles; Kalman filtering; computationally efficient diagnosis system; active fault diagnosis; artificial excitation system